Certain remarks on a class of evolution quasi-variational inequalities - A. H. Siddiqi; Pammy Manchanda (International Journal of Mathematics and Mathematical Sciences)
We prove two existence theorems, one for evolution quasi-variational inequalities and the other for a time-dependent quasi-variational inequality modeling the quasi-static problem of elastoplasticity with combined kinetic-isotropic hardening.